Improvement of transient stability of power systems with STATCOM-controller using trajectory sensitivity - Chatterjee, D.; Ghosh, Arindam (Elsevier Ltd, 2011)
This paper discusses the use of trajectory sensitivity analysis (TSA) in determining the transient stability margin of a power system compensated by a shunt FACTS device. The shunt device used is static synchronous compensator (STATCOM). It is shown that TSA can be used for the design of controller for the STATCOM. The preferable locations for the placement of the STATCOM for different fault conditions are also identified. The effects of STATCOM in maintaining different bus voltages in the post-fault condition are studied. The STATCOM is modeled by a voltage source connected to the system through a transformer. The systems used for the study are the WSCC 3-machine 9-bus system and the IEEE 16-machine 68-bus system.